(untitled) (Global Journal of Human-Social Science, 2017)
Of the most commonly celebrated propositions in international trade is the hypothesis that trade liberalization is associated with declining prices so that protectionism is inflationary The New Growth Theory is strongly in favor of this view However the Cost-push advocators claim for the existence of positive correlations between trade openness and inflation variables Moreover empirical studies have been confirming inconclusive results regarding the nature of relationships between the two variables These theoretical and empirical departures are the principal motivations to the current study This study is aimed to test the relationship between inflation and trade openness variables in Ethiopia using the time series data set for the period serially ranging from 1976 77 to 2016 77 Augmented Dickey Fuller and Phillips Perron approaches will be employed for testing the stationarity properties of individual variables in the model and the Johnson s maximum likely-hood approach will be employed for cointegration tests Finally Vector Error Correction will be estimated in order to determine the relationships among variables entered the inflation model adopted both in the short and the long run periods